Inorganic silicon modified water-based corrosion-inhibition anticorrosive paint containing functional polysiloxane as well as preparation method and application of inorganic silicon modified water-based corrosion-inhibition anticorrosive paint
By combining functional polysiloxane with inorganic silicone-based corrosion inhibiting filler and combining with aqueous hybrid acrylic emulsion, a dense physical barrier and active corrosion inhibiting layer is formed, which solves the problems of insufficient drying speed, hardness and salt spray resistance of water-based anticorrosion coatings, and achieves efficient corrosion resistance and adapts to the demanding requirements of the marine environment.
Patent Information
- Application Number
- CN202510555039.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-08-15
- Estimated Expiration
- 2045-04-29
AI Technical Summary
The existing water-based anticorrosion coatings have shortcomings in terms of drying speed, hardness, viscosity, long-term water and salt spray resistance and paint film density, which is difficult to meet the strict requirements of ships in high humidity environments.
Functional polysiloxane is combined with inorganic silicone-based corrosion inhibiting filler, combined with aqueous hybrid acrylic emulsion, to form a dense physical barrier and active corrosion inhibiting layer. Through the synergistic effect of calcium ion-exchange silicone pigment and calcium silicate, the weather resistance and corrosion resistance of the coating are improved.
It achieves rapid drying, high hardness, low VOC emissions, anti-resistance and long-term anti-corrosion properties, especially in marine environments, which show excellent water, salt spray resistance and scratch protection.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of anti-corrosion coatings and relates to an inorganic silicon-modified water-based corrosion-inhibiting anti-corrosion coating containing functional polysiloxane, a preparation method and an application thereof. Background Art
[0002] In the harsh marine environment, ships and their marine engineering structures are constantly exposed to high salt spray, high humidity, strong ultraviolet radiation, and erosion from waves, which places extremely stringent requirements on the performance of anti-corrosion coatings. Although traditional solvent-based heavy-duty anti-corrosion coatings have reliable performance, their high VOC emissions pose a threat to the enclosed cabin environment and port air quality, and are increasingly restricted. Existing water-based anti-corrosion coatings, although they have advantages in environmental protection, are often difficult to fully meet the requirements of heavy-duty anti-corrosion when applied to the shipbuilding field due to their resistance to salt water immersion, anti-penetration, paint film density, and long-term weather resistance. In particular, problems such as flash rust, slow drying, and tolerance for complex steel structure surface treatments that are prone to occur during construction in high humidity environments limit their widespread application in key areas such as ship primers, ballast tanks, and decks.
[0003] Currently, common waterborne anticorrosive coating systems include waterborne acrylics, waterborne alkyds, waterborne epoxy esters, two-component waterborne epoxies, and two-component waterborne polyurethanes. However, these systems still have some shortcomings. For example, one-component waterborne acrylic coatings are prone to flash rust and back-tack under high temperature and humidity conditions, and their hardness builds slowly. Waterborne alkyd and epoxy ester coatings dry slowly and have low hardness. While two-component systems offer better performance, they suffer from pot life limitations, inconvenient construction, and high costs. To address these issues, researchers have experimented with modifying waterborne resins with inorganic materials or using novel corrosion-inhibiting pigments. For example, inorganic silicon corrosion-inhibiting pigments (such as calcium ion-exchange silica pigments and calcium silicate) have been used to replace traditional anticorrosive pigments containing heavy metals or with poor stability. Furthermore, waterborne hybrid acrylic emulsions have been employed as film-forming agents to improve the coating's fast-drying properties, hardness, water resistance, and corrosion resistance.
[0004] Due to its unique Si-O-Si backbone structure, polysiloxanes possess excellent resistance to high and low temperatures, weathering, UV rays, low surface energy, high hydrophobicity, and good biocompatibility. Incorporating polysiloxanes into coating systems is expected to significantly enhance the coating's weather resistance, hydrophobicity, stain resistance, and flexibility. However, a mature solution remains to effectively and stably combine polysiloxanes with water-based inorganic modification systems (particularly those containing inorganic corrosion-inhibiting pigments and inorganic hybrid emulsions) to leverage their synergistic effects and enhance the overall corrosion protection performance of the coating.
[0005] Therefore, developing a water-based anti-corrosion coating that is environmentally friendly, easy to construct, and has excellent long-term protective performance, especially one that can adapt to the harsh requirements of the marine environment, is of great significance to the sustainable development of the shipbuilding industry. Summary of the Invention
[0006] The technical problem to be solved by the present invention is as follows: The present invention aims to overcome the shortcomings of existing water-based anti-corrosion coatings in terms of drying speed, hardness, back adhesion, long-term water and salt spray resistance, and paint film density, and provide an inorganic silicon-modified water-based corrosion-inhibiting anti-corrosion coating containing functional polysiloxane that has low VOC content, does not contain heavy metals, dries quickly, has high hardness, and has excellent water and salt spray resistance, especially with enhanced paint film density and hydrophobicity, and long-term anti-corrosion performance, and a preparation method thereof.
[0007] In order to achieve the above, the present invention provides an inorganic silicon modified water-based corrosion inhibition and anticorrosion coating containing functional polysiloxane, the raw material components of which include, by weight: Water-based hybrid acrylic emulsion: 30-60 parts (based on solid content); functional polysiloxane: 1-15 parts (based on solid content); inorganic silicon-based corrosion inhibitor filler: 5-25 parts; pigments and fillers: 10-40 parts; water-based additives: 1-5 parts; water: the balance, add to 100 parts.
[0008] Preferably, the solid content of the aqueous hybrid acrylic emulsion is 40-55 wt %.
[0009] More preferably, the water-based hybrid acrylic emulsion is RJ-630 water-based hybrid acrylic emulsion.
[0010] Preferably, the functional polysiloxane is selected from at least one of the following: amino-functional polysiloxane emulsion or aqueous dispersion; silanol- or alkoxy-functional polysiloxane emulsion or aqueous dispersion.
[0011] The amino-functionalized polysiloxane emulsion or aqueous dispersion is specifically Shin-Etsu KF-8010. The silanol- or alkoxy-functionalized polysiloxane emulsion or aqueous dispersion is specifically SILRES® BS 4004.
[0012] These functional groups of the functional polysiloxane help the polysiloxane to physically entangle or chemically crosslink with the components in the water-based hybrid acrylic emulsion or coating, improve its compatibility and stability in the system, and enhance the crosslinking density and performance of the paint film.
[0013] Preferably, the inorganic silicon-based corrosion-inhibiting filler is selected from at least one of the following: calcium ion exchange silica gel pigment; calcium silicate; calcium silicon phosphate.
[0014] More preferably, the inorganic silicon-based corrosion-inhibiting filler comprises a combination of at least two selected from calcium ion-exchange silica gel pigments, calcium silicate and calcium silicate phosphate.
[0015] Particularly preferably, the inorganic silicon-based corrosion-inhibiting filler is a combination of calcium ion-exchange silica gel pigment and calcium silicate, wherein the weight ratio of the calcium ion-exchange silica gel pigment to the calcium silicate is 1:3 to 3:1.
[0016] The present invention preferably utilizes a combination of at least two different types of inorganic silicon-based corrosion-inhibiting fillers: calcium ion-exchange silica pigment and calcium silicate. The calcium ion-exchange silica pigment rapidly releases calcium ions, providing timely passivation and pH buffering at the initial stages of corrosion or where the paint film is damaged, effectively inhibiting the spread of rust in pitting and scratches. Calcium silicate, on the other hand, continuously releases silicate ions, reacting with the metal substrate to form a more stable and dense silicate conversion film, providing long-lasting physical shielding and chemical passivation.
[0017] Preferably, the pigments and fillers are selected from at least one of conventional pigments and fillers such as titanium dioxide, iron oxide pigment, mica powder, talc, barium sulfate, and kaolin.
[0018] Preferably, the aqueous additive is selected from at least one of a wetting agent, a dispersant, a defoaming agent, a leveling agent, a thickener, a film-forming aid, and a pH adjuster. The film-forming aid is preferably a low-VOC or zero-VOC film-forming aid.
[0019] The present invention also provides a method for preparing the above-mentioned coating, comprising the following steps: (S1) adding an inorganic silicon-based corrosion inhibitor filler and a pigment filler into water, dispersing them at high speed in the presence of a wetting agent and a dispersant, and grinding them to a specified fineness to prepare a pigment slurry; (S2) adding the aqueous hybrid acrylic emulsion and the functional polysiloxane to the pigment slurry obtained in (S1) under stirring; (S3) adding other water-based additives (such as defoaming agent, leveling agent, thickener, film-forming agent) and the remaining water in sequence, stirring evenly, adjusting the viscosity and pH value according to actual needs, filtering, and obtaining the coating.
[0020] The coating prepared by the present invention has environmental protection, construction convenience and excellent long-term protective performance, and is particularly a water-based anti-corrosion coating that can adapt to the harsh requirements of the marine environment.
[0021] Compared with the prior art, the present invention has the following significant advantages: (1) The present invention organically combines an inorganic silicon-based corrosion-inhibiting filler, a water-based hybrid acrylic emulsion, and a functional polysiloxane. The functional polysiloxane can better disperse and possibly participate in the film-forming process, filling the micropores of the paint film to form a denser physical barrier. At the same time, its low surface energy and hydrophobicity significantly reduce the penetration of water and corrosive media. The inorganic silicon corrosion-inhibiting pigment plays a corrosion-inhibiting role at the interface, especially inhibiting the spread of corrosion when the paint film is slightly damaged. This multiple effect of "physical barrier enhancement + active corrosion inhibition + surface hydrophobic modification" significantly improves the long-term water resistance and salt spray resistance of the coating, especially the ability to resist corrosion extension in scratched areas.
[0022] (2) Water-based hybrid acrylic emulsions inherently have a fast drying speed and high early hardness. The introduction of functional polysiloxanes (especially those that can participate in cross-linking) can further increase the cross-linking density of the paint film, allowing the coating to dry quickly while achieving a higher final hardness (up to H or higher) and effectively improving the high-temperature back-tack problem. At the same time, the flexibility of the polysiloxane chain segments helps maintain or improve the flexibility and impact resistance of the coating.
[0023] (3) The present invention is a water-based system, and the VOC content can be controlled at a low level (e.g., ≤100 g / L, or even lower). It does not contain toxic heavy metal corrosion inhibitors and meets environmental protection requirements. The coating is a single component, stable in storage, and easy to apply. It can be applied by conventional methods such as spraying and brushing.
[0024] (4) The present invention introduces specific functional polysiloxanes into a specific water-based anticorrosion system comprising an inorganic silicon-based corrosion inhibitor filler and a water-based hybrid acrylic emulsion. This achieves a comprehensive effect in terms of improving the density, hydrophobicity, long-term salt spray resistance, and hardness of the paint film while simultaneously overcoming the back-sticking problem. Functional polysiloxanes are not simply physically added; their functional groups enable them to be more effectively anchored in the system or participate in film formation. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be described in detail below with reference to specific embodiments. It should be noted that the following embodiments are only exemplary illustrations of the present invention and are not intended to limit the scope of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
[0026] Unless otherwise specified, parts used in the examples are parts by weight.
[0027] Raw materials: Water-based hybrid acrylic emulsion, RJ-630 water-based hybrid acrylic emulsion, solid content about 50%, commercially available, Shenzhen Ruijing New Material Technology Co., Ltd.
[0028] Water-based acrylic emulsion: ordinary pure acrylic emulsion, solid content of about 50%, commercially available from BASF.
[0029] Amino-functional polysiloxane emulsion: Shin-Etsu KF-8010, amino value approximately 0.3 mmol / g (solid content), solid content approximately 50%.
[0030] Non-functional polysiloxane emulsion E (PDMS emulsion): commercially available, hydroxyl-terminated or non-functional, solid content approximately 50%.
[0031] Calcium ion exchange silica pigment: HOMAC® LM-50, Lingwei Technology; Calcium silicate: commercially available, average particle size 5-15 μm.
[0032] Titanium dioxide R-902: Commercially available. Mica powder: Commercially available, wet process, 200 mesh.
[0033] Wetting agent: BYK-348. Dispersant: Water-based sodium polyacrylate dispersant. Defoamer: BYK-028. Coalescing agent: Texanol (Dow Chemical). Thickener and pH adjuster can be added as needed (preferred thickener: associative polyurethane thickener. pH adjuster: AMP-95).
[0034] Coating preparation method: (1) According to the formula of each example or Table 1, water, wetting agent, dispersant and half of the defoaming agent are added to a dispersion tank, stirred evenly, and then inorganic silicon-based corrosion inhibitor filler and pigment filler are added. The mixture is dispersed at high speed (1500-2000 rpm) for 30 minutes, and then ground with a sand mill to a fineness of ≤40μm to obtain a pigment slurry.
[0035] (2) Slowly add the (water-based hybrid acrylic emulsion or water-based acrylic emulsion) and the polysiloxane emulsion into the pigment slurry under low-speed stirring.
[0036] (3) Then add the remaining additives (film-forming additive, remaining defoamer) in sequence and adjust to the application viscosity with deionized water. Stir evenly and filter the material.
[0037] Example 1: The coating raw material components are, by weight: 35 parts of aqueous hybrid acrylic emulsion (based on solid content); 4.0 parts of amino-functionalized polysiloxane emulsion (based on solid content); 8 parts of calcium ion exchange silica gel pigment; 7.0 parts of calcium silicate; 10 parts of titanium dioxide R-902; 3.5 parts of aqueous additive; and the balance of water, added to 100 parts.
[0038] Example 2: The coating raw material components are as follows, by weight: water-based hybrid acrylic emulsion: 40 parts (based on solid content); amino-functionalized polysiloxane emulsion: 2.0 parts (based on solid content); calcium ion exchange silica gel pigment: 6 parts; calcium silicate: 5.0 parts; titanium dioxide R-902: 12 parts; water-based additive: 3.8 parts; water: the balance, added to 100 parts.
[0039] Example 3: The coating raw material components are as follows, by weight: aqueous hybrid acrylic emulsion: 45 parts (based on solid content); amino-functionalized polysiloxane emulsion: 3.2 parts (based on solid content); calcium ion exchange silica pigment: 10 parts; calcium silicate: 8.0 parts; titanium dioxide R-902: 15 parts; water-based additive: 4.0 parts; water: the remainder, added to 100 parts.
[0040] Comparative Example 1: Compared with Example 1, Comparative Example 1 differs in that the amino-functional polysiloxane is replaced with a conventional non-functional polysiloxane, and the other operations are the same as those in Example 1.
[0041] Comparative Example 2: Compared with Example 1, Comparative Example 2 differs in that the inorganic silicon-based corrosion-inhibiting fillers are all replaced with calcium ion-exchange silica gel pigments. Other operations are the same as in Example 1.
[0042] Comparative Example 3: Compared with Example 1, Comparative Example 3 differs in that the inorganic silicon-based corrosion inhibitor filler is completely replaced with calcium silicate. Other operations are the same as in Example 1.
[0043] Comparative Example 4: Compared with Example 1, Comparative Example 4 differs in that the inorganic silicon-based corrosion inhibitor filler is completely replaced with zinc phosphate. Other operations are the same as in Example 1.
[0044] Comparative Example 5: Compared with Example 1, Comparative Example 5 differs in that the inorganic silicon-based corrosion inhibitor filler is replaced with 8 parts of calcium ion exchange silica gel pigment and 7 parts of zinc phosphate. Other operations are the same as in Example 1.
[0045] Comparative Example 6: Compared with Example 1, Comparative Example 6 differs in that the aqueous hybrid acrylic emulsion is replaced with an aqueous acrylic emulsion (ordinary pure acrylic emulsion), and other operations are the same as those in Example 1.
[0046] Table 1:
[0047] Performance testing: The prepared coating was sprayed onto Q235 steel panels sandblasted to Sa 2.5, with a dry film thickness of (60 ± 5) μm. Performance tests were then conducted after curing for 7 days under standard conditions (23 ± 2°C, 50 ± 5% RH).
[0048] Testing standards: Surface dry / through dry time: GB / T 1728-1979; Hardness (pencil method): GB / T 6739-2006; Adhesion (cross-hatch method): GB / T 9286-1998; Water resistance: GB / T 1733-1993 (immersion time as required); Neutral salt spray resistance: GB / T 1771-2007 (scratch specimen, observe blistering, rusting, peeling and corrosion extension width on both sides of the scratch), 240h, 480h.
[0049] Tack: Place the coated sample in a 50℃ oven for 1 hour. Immediately press it with your fingers after taking it out to observe whether there is sticky fingers or indentation.
[0050] Contact angle: A contact angle meter is used to measure the static contact angle of a water droplet on the coating surface.
[0051] Table 2
[0052] In Comparative Example 1, replacing the functionalized siloxane with a non-functionalized siloxane resulted in a decrease in hardness from H to HB, slight tack, poor long-term salt spray resistance (blistering and scratch growth after 480 hours), and a significant decrease in contact angle (95° vs. 105°). This demonstrates the critical role of the functional groups in polysiloxane in improving coating hardness, anti-tack, long-term corrosion protection, and surface hydrophobicity. Comparative Example 2 used only calcium ion-exchange silica pigment, and Comparative Example 3 used only calcium silicate. Both exhibited significantly reduced neutral salt spray resistance compared to Example 1 (particularly scratch growth after 240 hours and overall performance after 480 hours). Comparative Example 3 (using only calcium silicate) performed particularly poorly. This strongly demonstrates the significant synergistic corrosion inhibition effect of calcium ion-exchange silica pigment and calcium silicate in the system of the present invention, surpassing the use of either component alone.
[0053] Comparative Example 4 used traditional zinc phosphate instead of the calcium ion-exchange silica gel pigment and calcium silicate combination, while Comparative Example 5 used a calcium ion-exchange silica gel pigment and zinc phosphate combination. The results showed that the salt spray resistance (especially scratch protection and long-term performance) of Comparative Examples 4 and 5 were inferior to that of Example 1. While the F+H combination in Comparative Example 5 outperformed the H alone in Comparative Example 4, it was still inferior to that of Example 1. This demonstrates that the preferred composite inorganic silicon-based corrosion inhibitor combination of the present invention, in specific hybrid / functional siloxane systems, has superior corrosion protection to traditional zinc phosphate or calcium ion-exchange silica gel pigment and zinc phosphate combinations.
[0054] In Comparative Example 6, replacing the hybrid emulsion with a standard pure acrylic emulsion resulted in slower drying speed, significantly reduced hardness, severe back-tack, poorer water resistance, and a sharp deterioration in salt spray resistance (especially long-term and scratched). The contact angle was also the lowest. This clearly demonstrates that high-performance water-based hybrid acrylic emulsions are fundamental and a key component in achieving the excellent properties of fast drying, high hardness, anti-back-tack, and strong protection described in this invention.
[0055] This invention combines a specific waterborne inorganic hybrid acrylic emulsion, a functional polysiloxane, and a composite corrosion inhibition system composed of a preferred calcium ion-exchange silica gel pigment and calcium silicate, leveraging their significant synergistic effect to successfully produce a waterborne corrosion-inhibiting anticorrosive coating with excellent overall performance. While maintaining its environmentally friendly properties, this coating demonstrates outstanding drying speed, hardness, anti-blocking properties, surface hydrophobicity, and long-term corrosion protection (particularly for scratched areas), significantly outperforming comparative systems using non-functional siloxanes, single corrosion inhibitors, traditional corrosion inhibitors, or conventional acrylic emulsions. Waterborne anticorrosive coatings that can withstand the demanding demands of marine environments are of great significance to the development of the marine industry.
[0056] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be included within the scope of protection of the present invention.
Claims
1. An inorganic silicon modified water-based corrosion inhibition and anticorrosion coating containing functional polysiloxane, characterized in that: The raw material components include, by weight: 30-60 parts of water-based hybrid acrylic emulsion, calculated by solid content; 1-15 parts of functional polysiloxane, calculated by solid content; 5-25 parts of inorganic silicon-based corrosion-inhibiting filler; 10-40 parts of pigments and fillers; 1-5 parts of water-based additives; and water as the balance, added to 100 parts. The functional polysiloxane is selected from at least one of amino-functionalized polysiloxane emulsions or aqueous dispersions, and silanol- or alkoxy-functionalized polysiloxane emulsions or aqueous dispersions. The inorganic silicon-based corrosion-inhibiting filler is selected from at least one of calcium ion-exchange silica gel pigments, calcium silicate, and calcium silicon phosphate.
2. The inorganic silicon modified water-based corrosion inhibition and anticorrosion coating containing functional polysiloxane according to claim 1, characterized in that: The water-based hybrid acrylic emulsion is RJ-630 water-based hybrid acrylic emulsion.
3. The inorganic silicon modified water-based corrosion inhibition and anticorrosion coating containing functional polysiloxane according to claim 1, characterized in that: The amino-functionalized polysiloxane emulsion or aqueous dispersion is KF-8010; the silanol- or alkoxy-functionalized polysiloxane emulsion or aqueous dispersion is SILRES® BS 4004.
4. The inorganic silicon modified water-based corrosion inhibition and anticorrosion coating containing functional polysiloxane according to claim 1, characterized in that: The inorganic silicon-based corrosion-inhibiting filler comprises a combination of at least two selected from calcium ion-exchange silica gel pigments, calcium silicate and calcium silicate phosphate.
5. The inorganic silicon modified water-based corrosion inhibition and anticorrosion coating containing functional polysiloxane according to claim 4, characterized in that: The inorganic silicon-based corrosion-inhibiting filler is a combination of calcium ion-exchange silica gel pigment and calcium silicate.
6. The inorganic silicon modified water-based corrosion inhibition and anticorrosion coating containing functional polysiloxane according to claim 5, characterized in that: The weight ratio of the calcium ion exchange silica gel pigment to calcium silicate is 1:3 to 3:
1.
7. The inorganic silicon modified water-based corrosion inhibition and anticorrosion coating containing functional polysiloxane according to claim 1, characterized in that: The pigment and filler are selected from at least one of titanium dioxide, iron oxide pigment, mica powder, talc, barium sulfate, and kaolin; the aqueous additive is selected from at least one of a wetting agent, a dispersant, a defoaming agent, a leveling agent, a thickener, a film-forming aid, and a pH regulator.
8. A method for preparing the coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Adding inorganic silicon-based corrosion inhibitor fillers and pigment fillers to water, dispersing and grinding at high speed to a specified fineness in the presence of a wetting agent and a dispersant to prepare a pigment slurry; (2) adding the aqueous hybrid acrylic emulsion and the functional polysiloxane to the pigment slurry obtained in step (1) under stirring; (3) Add other water-based additives and the remaining water in sequence, stir evenly, adjust to the construction viscosity, and filter to obtain the coating.
9. Use of the coating according to any one of claims 1 to 7, characterized in that: Application of inorganic silicon modified water-based corrosion inhibition and anti-corrosion coatings containing functional polysiloxane in the field of ship corrosion protection in marine environments.
Citation Information
Patent Citations
Organic silicon / hydroxyl phosphate composite modified water emulsion acrylic resin and preparation method and application thereof
CN101775101A
Waterborne acrylic primer
CN108441055A
Modified acrylic polysiloxane coating and preparation method thereof
CN113292875A
Environment-friendly single-component water-based acrylic acid antirust coating
CN115975449A
Chromium-free anticorrosive coating compositions and articles made therefrom
CN116355489A
Cited By
Steel structure building steel surface heat insulation fireproof coating and preparation method thereof
CN122213856A